European Instructional Lectures Volume 10, 2010; 11th EFORT Congress, Madrid, Spain - Bentley, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This tenth volume in the EUROPEAN INSTRUCTIONAL LECTURES series continues the format of educational chapters from across Orthopaedics and Traumatology contributed by notable surgeons in Europe. It provides up-to-date material and major advances covering a range of topics including: -General Orthopaedics -Musculo-Skeletal Tumours -Paediatric Orthopaedics -Trauma -Spine -Upper Limb -Hip -Knee -Ankle and Foot All the lectures were presented at the 11th EFORT Congress in Madrid, Spain. The lectures are an authoritative source of information illustrated by radiographs, MRI and CT Scans, operative photographs, tables and line drawings. They are a valuable source of instruction for Surgeons and Trainees alike. This book has been edited by Professor George Bentley. Chairman of Scientific Publications Committee of EFORT.
General Orthopaedics -- Necrotising Fasciitis -- Trauma: Non-Union: New Trends -- Bone and Joint Tumors -- Bone Tumours: Work Up 2009 -- Diagnosis and Treatment of Soft Tissue Sarcomas -- Paediatrics -- Management of Lower Limb Deformities -- Total Hip Replacement in the Congenitally Dislocated Hip Using the Paavilainen Technique -- Trauma -- Operative Strategy for Fracture-Dislocation of the Elbow -- Fractures of the Scaphoid: Diagnosis and Management -- Spine -- Treatment of Thoraco-Lumbar Fractures -- The Rheumatoid Cervical Spine -- Upper Limb -- Partial Rotator Cuff Ruptures -- Massive Tears of the Rotator Cuff -- Hip -- Hip Resurfacing -- Knee -- Total Knee Arthroplasty in Extra-Articular Deformities -- Unicompartmental Knee Arthroplasty -- Isolated Patellofemoral Osteoarthritis -- Foot/Ankle -- Achilles Tendinopathy -- The Painful Flatfoot.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Medicine & Public Health; Orthopedics; Surgical Orthopedics; Conservative Orthopedics